2020
DOI: 10.1186/s13731-020-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of the influence of the university’s environment and support system on the precursors of social entrepreneurial intention of students

Abstract: This systematic literature review aims at understanding the influence of the university's environment and support system (ESS) in shaping the social entrepreneurial intention (SEI) of post-secondary education students. Social entrepreneurs play an important role in the economic and social developments of the communities in which they operate, thus many post-secondary institutions are starting to encourage more students to engage in social entrepreneurial behaviour. Consequently, there is a need for systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 177 publications
(316 reference statements)
4
68
0
3
Order By: Relevance
“…Third, we found that perceptions of education and training are positively correlated with college students' entrepreneurial motivations, which was in line with the conclusions drawn by a variety of scholars such as Sirbu et al (2015), Hou et al (2019), and Bazan et al (2020). This attested to the effectiveness of entrepreneurship education in higher education institutions in nurturing college students' entrepreneurial spirits, creating a rich entrepreneurial atmosphere, and fostering students' entrepreneurial interests and enthusiasm.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Third, we found that perceptions of education and training are positively correlated with college students' entrepreneurial motivations, which was in line with the conclusions drawn by a variety of scholars such as Sirbu et al (2015), Hou et al (2019), and Bazan et al (2020). This attested to the effectiveness of entrepreneurship education in higher education institutions in nurturing college students' entrepreneurial spirits, creating a rich entrepreneurial atmosphere, and fostering students' entrepreneurial interests and enthusiasm.…”
Section: Discussionsupporting
confidence: 89%
“…Preferential measures for entrepreneurs offered by government departments in taxation, facilitation of approval processes, and optimization of entrepreneurial institutions Gnyawali and Fogged, 1994;Garcia-Cabrera et al, 2018;Nam and Hwansoo, 2019 Socio-economic conditions Level of development of the local economy, industrial structure, and urban construction; infrastructure such as transport, water supply, and electricity supply; and regional entrepreneurial culture Davidsson and Honig, 2003;Liñán and Santos, 2007;Gathungu and Baariu, 2018;Martínez-Fierro et al, 2020 Education and training Innovation and entrepreneurship education, related activities, and capacity-building training attended by entrepreneurs during their studies Turker and Selcuk, 2009;Sirbu et al, 2015;Bazan et al, 2020 Financial support Financial support obtained by entrepreneurs in sources of financing, interest-free loans, and start-up funds Kristiansen and Indarti, 2004;Welter, 2011;Yao et al, 2016 Non-financial support Assistance received by entrepreneurs in expert guidance, development opportunities, information, and resources Djankov et al, 2006;Schwartz, 2009;Gathungu and Baariu, 2018 attitudes and behaviors. Based on the above viewpoints, we hypothesized the following.…”
Section: Government Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, recent research on social entrepreneurship education indicates that cross organizational cooperation is an important trend in the cultivation of social entrepreneurship talents. For example, Bazan et al (2020) point out that the integration of the external environment and colleges' initiative play an important role in promoting students' social entrepreneurship learning. Some scholars also pointed out that the construction of college students' entrepreneurial environment will help to enhance students' social entrepreneurial willingness.…”
Section: Social Entrepreneurship's Cultivation Model In Colleges and mentioning
confidence: 99%
“…The factors influencing ELE include internal factors and external factors; internal factors are mainly characteristic variables, which are usually difficult to change ( Hu and Yuan, 2020 ). With increasing researches on positive psychology and behavior, the construction of positive behavior standards (PC), which conforms to development-, measurement-, and performance-oriented characteristics, begins to receive extensive attention ( Bazan et al, 2020 ). Entrepreneurship learning is not all smooth sailing, and due to differences in individual character and psychological quality, college students have different levels of acceptance toward entrepreneurship education in colleges ( Liu and Chen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%